First and second trimester bleeding and pregnancy outcome: a prospective study in a tertiary government hospital - M., Chaithra; S., Anitha G.; Suresh, Sukanya; C., Savitha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: Bleeding in first and second trimester of pregnancy is one of the common complications of pregnancy. there is evidence from various prospective and retrospective studies that first and second trimester vaginal bleeding which continue with pregnancy is associated with adverse pregnancy outcome, including preterm delivery, low birth weight babies, perinatal death and congenital anomalies. Objective of this study was to know the outcome of pregnancies who have bleeding in first and second trimester of pregnancy. Methods: This study was prospective study done in the department of obstetrics and gynaecology, Vanivilas Hospital, Bangalore from September 2018 to August 2019. Results: This study concludes that I trimester vaginal bleeding are at increased risk of abortion than in II trimester vaginal bleeding. Risk of placenta previa was more in II trimester vaginal bleeding than in I trimester vaginal bleeding. Conclusions: This study concludes that I trimester vaginal bleeding are at increased risk of abortion than in II trimester vaginal bleeding. Risk of placenta previa was more in II trimester vaginal bleeding than in I trimester vaginal bleeding. Bleeding in I trimester and II trimester call for special attention in view of increased risk of preterm birth and perinatal death. Recognition of these association will be useful for detection and follow up of pregnancies being at high risk.